RANCANG BANGUN APLIKASI MANAJEMEN SURAT BERBASIS WEB PADA DINAS PERHUBUNGAN KOTA SURABAYA - Nanda lutfian gunawan; Antok Supriyanto; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Abstract: Department of Transportation is implementing elements of regional autonomy, which hold the majority of regional government affairs, the field of Communications., The Department of Transportation to apply timeliness in doing recording, reporting Letters, Department of Transportation often have inaccuracies in the distribution of letter, it made the performance becomes late addition to distribution, There are difficulties experienced by secretary part, these difficulties such as the mail storage (archiving). During the archiving process is done well. However, for the maintenance of the archives of the letter can be accomplished and is still experiencing some difficulties, difficulty finding process letter, affect the shrinkage process should be done by letter secretary section.Through the analysis, to overcome the experiences to which there is by utilizing information technology based on the concept of mail management to support the process receiving, data collection, distribution, archiving, anddeliveryofletters.Based on the results of testing and evaluation, it is known that the web-based management application letter can provide ease of Acceptance of incoming mail from internal and external, to record, archive and distribute up to send mail out.